Comparative Study on Ontology Management Approaches in Semantic Web - Jain, Ranjna; Duhan, Neelam; Sharma, AK (International Journal of Computer Sciences and Engineering, 2025)
Ontology defines a common vocabulary which includes machine interpretable definitions of basic concepts in the domain and relation among them for researchers who need to share information in a domain. But in actual, in place of reusing existing ontologies of required domain, domain experts create their own ontology leading in formation of multiple ontologies of the same domain containing incomplete concepts and relations. This causes ontology heterogeneity and inconsistency problem. For better and precise results managing, these heterogeneous ontologies are necessary. A large number of work has been done in the recent past for managing the existing ontologies so that they can be reused for data integration, information integration, data warehousing and other fields. This paper provides different approaches that have been used in the recent years for managing these ontologies.